Characterization and within-tree variation of wood anatomy of Acacia melanoxylon - Antonio JA Santos; Helena Pereira; Ofélia Anjos (Instituto Politécnico de Viseu, 2018)
Introduction: A. melanoxylon wood has a large commercial application given its anatomical characteristics and mechanical properties. However studies on the anatomical characterisation of this species grown in Portugal are scarce. Objectives: To describe the transverse anatomical characteristics and their within-tree variation of A. melanoxylon trees growing in Portugal. Methods: 20 trees were analysed in transverse section for tree radial position (10%; 50%; 90%) and five height levels (base, 15%; 35%; 65%; 80%) in north and south directions. Measurements included: fibre diameter (m), fibre wall thickness (m), Runkle index; Flexibility index, vessel number (vessel number /mm2), porosity (%) and vessel width (m). Results: Earlywood fibres have lower wall thickness and higher lumen diameter than latewood fibres. Runkle and flexibility indexes confirm its potential for pulp and paper production. Porosity was lower near the pith as a result of a slight increase of vessel number with smaller size. Conclusion: Blackwood showed potential as an alternative species to supply the industry.